Feasible and effective control strategies on extreme emissions of chlorinated persistent organic pollutants during the start-up processes of municipal solid waste incinerators. (December 2020) - Cheruiyot, Nicholas Kiprotich; Yang, Hsi-Hsien; Wang, Lin-Chi; Lin, Chun-Chi
Abstract: A typical two-day start-up of municipal solid waste incinerators (MSWIs) can yield polychlorinated dibenzo- p -dioxin and dibenzofuran (PCDD/F) and polychlorinated biphenyl (PCB) emission quantities around 10 times higher than those from an entire year of normal operations, as measured in this study. Thus, we tested specific control strategies for inhibiting the formation of chlorinated persistent organic pollutants (Cl-POPs), namely, extensively cleaning the ash accumulated beneath the furnace bed of the combustion chamber and deposited on the walls of the superheater and economizer and shortening the residence time of the flue gas in the optimal temperature window for Cl-POP formation. Also, we advanced the injection times of the activated carbon and lime slurry to lower Cl-POP emissions during start-up. Our findings show that these strategies were highly effective and reduced the Cl-POP emissions by > 98%, most of which (96.4–98.2%) was attributable to inhibiting formation. In summary, the proposed control strategies require no modifications to existing air pollution control devices, have little influence on operational cost, and are effective and feasible for the majority of MSWIs. Graphical abstract: Image 1 Highlights: Start-up processes contribute 95% of the total annual PCDD/F emissions. The proposed control strategies reduce PCDD/F emissions by 99%. Inhibiting the formation of PCDD/Fs reduces their emission more effectively than enhancing the removal. These strategies require no modifications to existing control devices. Abstract : The proposed control strategies potentially reduce emissions of PCDD/Fs, PCBs, and PCDEs during the cold start-up of municipal solid waste incinerators (MSWIs) by > 98%.